2021
DOI: 10.1038/s41436-021-01260-4
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic variants in PCDHGC4 cause a novel neurodevelopmental syndrome with progressive microcephaly, seizures, and joint anomalies

Abstract: Purpose We aimed to define a novel autosomal recessive neurodevelopmental disorder, characterize its clinical features, and identify the underlying genetic cause for this condition. Methods We performed a detailed clinical characterization of 19 individuals from nine unrelated, consanguineous families with a neurodevelopmental disorder. We used genome/exome sequencing approaches, linkage and cosegregation analyses to identify disease-causing variants, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…It is likely that some of the primary roles that Pcdhγc4 has in the adjustment of cIN cell number to match the number of excitatory neurons apply also to the human cerebral cortex. Recent work suggests that Pcdhγc4 plays a critical role in human brain development as mutations in this gene are associated with a neurodevelopmental syndrome with progressive microcephaly and seizures (Iqbal et al, 2021). An understanding of the cell-cell interactions that use Pcdhγc4 to regulate cIN cell death should give fundamental insights into how the cerebral cortex forms and evolves.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that some of the primary roles that Pcdhγc4 has in the adjustment of cIN cell number to match the number of excitatory neurons apply also to the human cerebral cortex. Recent work suggests that Pcdhγc4 plays a critical role in human brain development as mutations in this gene are associated with a neurodevelopmental syndrome with progressive microcephaly and seizures (Iqbal et al, 2021). An understanding of the cell-cell interactions that use Pcdhγc4 to regulate cIN cell death should give fundamental insights into how the cerebral cortex forms and evolves.…”
Section: Discussionmentioning
confidence: 99%
“…The overall qualitative assessment of reporting was deemed “superficial/deficient” or “absent” in 87% (Domain I: Development, cognition, and mental health) to 98% (Domain IV: Pain, sleep, and quality of life) of papers (Figure 1). Five (2.5% of 200) reports were deemed “strong” in any single domain (pertaining to the genetic conditions associated with variants in the genes ADARB1 33 , GNAI1 34 , NCAPG2 35 , PCDHGC4 36 , and SPTBN1 37 ). No reports were deemed “strong” in their reporting across each of Domains I-IV.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Garrett et al discovered that neuronal survival and postnatal viability are controlled solely by γC4 suggesting a function that is unique to this isoform (although it presumably requires β and/or other γ carriers to reach the cell surface) ( Garrett et al, 2019 ). Additionally, a recent paper by Iqbal et al has shown that genetic γC4 variants cause a neurodevelopmental disorder which is potentially linked to γC4’s role in programmed cell death of neuronal cells ( Iqbal et al, 2021 ). Below we report extensive biophysical interaction studies of C-type isoform ectodomains and report the first crystal structure of a trans dimer formed by γC4.…”
Section: Introductionmentioning
confidence: 99%